Calidad de servicios que ofrecen las empresas CNT E.P. y Claro en áreas urbanas y rurales de Calceta - Intriago Bravo, Erwin Bladimir (2013)
The purpose of evaluating the quality of service offered by the National Telecommunications Corporation against private enterprise course, in urban and rural areas of the city of Sock unfold in three stages allowed the investigation, we first determined the SERVQUAL model, one of the more attached methodologies to study the perceived quality of the service users reflected in deductive logic, and literature, which helped meet the five dimensions for a series of questions developed in the second stage to assess perceptions through interviews with internal staff and external user surveys, tabulated in SPSS 11.5 statistical programs and REDATAM, which went to make a matrix to evaluate external customer perceptions and SWOT analysis showed competitive environmental factors to which facing the institution, and stating that to compete with a multinational company requires more effort and dedication from each of the partners. There was then, the third step in developing strategic proposals for measures to improve the dispersion between the gaps of service quality, prevailing prioritize dimensions and attributes, in order to provide alternatives to contribute to a guide in the performance of the CNT EP actions and pointing at it, service excellence, customer satisfaction and loyalty are essential for competitiveness, achievement and business success in the current globalization of the domestic and international market.